2006
DOI: 10.1111/j.1095-8312.2006.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological differentiation patterns between sister species: the case of Onthophagus taurus and Onthophagus illyricus (Coleoptera, Scarabaeidae)

Abstract: The present study investigated the morphological and genetic differentiation pattern between two sympatric dung beetle sister species, Onthophagus taurus and Onthophagus illyricus . The geometric morphometric approach coupled with the use of molecular markers allowed examination of the nature of interspecific relationships and an outline of the evolutionary and geographical processes that might have led to interspecific differentiation and the present-day partial sympatric and syntopic pattern of distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 86 publications
(97 reference statements)
4
46
0
3
Order By: Relevance
“…Previous studies showed that head shape varies in relation to horn size Pizzo et al 2006b), which was interpreted as a balancing static system compensating barycentre backing due to horn protrusion in major males. The observed shape modifications also confer a relatively large and solid appearance on major males, which is likely to be advantageous in aggressive encounters.…”
Section: Other External Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that head shape varies in relation to horn size Pizzo et al 2006b), which was interpreted as a balancing static system compensating barycentre backing due to horn protrusion in major males. The observed shape modifications also confer a relatively large and solid appearance on major males, which is likely to be advantageous in aggressive encounters.…”
Section: Other External Structuresmentioning
confidence: 99%
“…If the evolution of some kind of compensation has the ability to reduce the costs associated with ornament development, then sexual selection may allow further exaggeration of ornaments over evolutionary time (Husak and Swallow 2011). It is also known that males bearing longer horns undergo morphological changes that confer higher success in male-male competition (Otte and Staymen 1979;Okada and Miyatake 2004;Okada et al 2007;Okada and Miyatake 2009;Pizzo et al 2006b). After initial contact, fighting Onthophagus males assume a typical position with the head and thorax held low, the abdomen held high, and the forelegs braced against the tunnel walls (Moczek and Emlen 2000).…”
Section: Other External Structuresmentioning
confidence: 99%
“…Die ermittelten Werte des Fixation Index (F ST ) nach Wright aus der AFLPAnalyse liegen für die Populationen von B. serricauda mit 0,2486 unterhalb des Wertes von 0,504, den Pizzo et al (2006) Ursachen für die Tatsache, dass genetische Unterschiede zwischen isolierten Populationen nicht in einen Zusammenhang mit ihrer räumlichen Distanz gesetzt werden können, sind zum einen in einem mangelnden genetischen Austausch und zum anderen in einer in kleinen Populationen auftretenden genetischen Drift zu suchen. Eine Zunahme der genetischen Differenz zwischen Teilpopulationen durch Isolation, die allerdings bei der Wintermotte Operophtera brumata mit einer Abnahme genetischer Differenzierung innerhalb untersuchter Teilpopulationen einhergeht, wurde von Van Dongen et al (1998) beschrieben.…”
Section: Distanz Zwischen Populationenunclassified
“…The developmental mechanisms of horns and their intra and interspecific expression patterns are well studied especially in Scarabaeidae: within this family, due to its large number of species and its morphological variability, Onthophagus is the most studied genus (Emlen, 1997;Emlen and Nijhout, 1999;Emlen et al, 2005;Moczek, 2011;Palestrini et al, 2000;Pizzo et al, 2006aPizzo et al, , b, 2012Macagno et al, 2009Macagno et al, , 2011a. Despite the wealth of studies on the Scarabaeidae, the horn expression pattern of the Geotrupidae, to our knowledge, has never been investigated.…”
Section: Introductionmentioning
confidence: 99%